Distribution of gelatinous fibers in seedling roots of living cycads. Issue 8 (1st August 2015) - Magellan, Tracy M.; Griffith, M. Patrick; Tomlinson, P. Barry
Abstract : Premise of the study: The presence of gelatinous (tension) fibers (GFs) in the roots of two extant cycadales ( Cycas and Zamia ) in a recent publication raises interesting issues of GF distribution in seed plants. An immediate question that arises from this discovery is whether GFs occur consistently in the radicle of all extant cycad genera and therefore might have a similar role in root contraction. We present results of a survey of nursery‐grown material of all 10 genera. Methods: We sequentially sectioned seedling root material and used simple staining and histochemical methods to follow anatomical changes along the radicle of all 10 genera. Key results: We found GFs in nine genera; Stangeria appears to be the only genus without them. In all genera, there is a wide variation in the number of GFs and also variation in the development of thickened, fleshy roots. "Tertiary expansion" is a useful term to describe late cell division and enlargement of both primary and secondary parenchyma, the latter produced by the vascular cambium. Certain other histological features can be diagnostically useful at the generic level. Conclusions: The functional interpretation of GFs as being wholly responsible for apparent tissue contraction is now somewhat compromised, especially as distortion of tracheary elements by changes in dimensions of parenchyma cells can falsely suggest root contraction when it may not occur. These preliminary results point the way to a more precise investigation of study material grown in more uniform environments using advanced technological methods.